2022
DOI: 10.1021/acsomega.1c04102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rice Seed Varieties Based on Near-Infrared Hyperspectral Imaging Technology Combined with Deep Learning

Abstract: Rice is one of the most important food crops in the world, and rice seed varieties are related to the yield and quality of rice. This study used near-infrared (NIR) hyperspectral technology with conventional machine learning methods (support vector machine (SVM), logistic regression (LR), and random forest (RF)) and deep learning methods (LeNet, GoogLeNet, and residual network (ResNet)) to establish variety identification models for five common types of rice seeds. Among the deep learning methods, the classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…The range of 900–980 nm was contributed to by the third overtone of C-H relevant to sugar [ 55 ]. For NIR spectra, wavelengths between 1050 nm and 1200 nm are mainly made up of the second overtone of C−H, and those between 1300 nm and 1500 nm are mainly related to the frequency of C-H [ 56 ]. The range of 1210–1450 nm is attributed to the 2nd overtone of C-H and the 1st overtone of O-H [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of 900–980 nm was contributed to by the third overtone of C-H relevant to sugar [ 55 ]. For NIR spectra, wavelengths between 1050 nm and 1200 nm are mainly made up of the second overtone of C−H, and those between 1300 nm and 1500 nm are mainly related to the frequency of C-H [ 56 ]. The range of 1210–1450 nm is attributed to the 2nd overtone of C-H and the 1st overtone of O-H [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used SVM [ 22 , 59 ], DT [ 59 ], KNN [ 59 ], or RF [ 18 ] to detect pesticide residue, which showed fine results. SVM [ 60 , 61 , 62 ], LR [ 63 ], CNN [ 31 , 56 , 64 ], RF [ 60 , 62 ], and ResNet [ 56 ] have been applied widely in quality detection of hyperspectral imaging. In this study, classic machine learning and deep learning methods, CNN, ResNet, LR, SVM, and RF, were used to achieve a multivariate analysis of the detection of pesticide residue levels in grapes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have researched the non-destructive identification of seed varieties based on hyperspectral imaging and machine learning or deep learning [ 4 , 9 , 17 , 18 , 24 26 , 48 , 49 ]. Although there might be a certain distance from the actual application due to a limited number of varieties in the training set, the successes of these studies guide the seed variety genuineness detection to ensure seed purity.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that the SVM and deep learning models are effective algorithms for processing large phenotypic spectral datasets. Even though the convolutional neural network (CNN) performs slightly better than the SVM in some cases, their overall performances are very close [ 49 ]. So, we chose the traditional machine learning algorithms (SVM, MLP, and RF) and got detection accuracy above 99% (SVM and MLP) that can be widely adopted, especially in resource-limited agricultural settings.…”
Section: Discussionmentioning
confidence: 99%
“…Te results showed that it could reduce the average absolute error and root mean square error. Jin et al [7] used the random forest algorithm to identify rice varieties. de Santana et al [8] used random forest and infrared spectra to detect food adulteration.…”
Section: Introductionmentioning
confidence: 99%